Transient meiotic arrest maintained by DON (6-diazo-5-oxo-l-norleucine) enhances nuclear/cytoplasmic maturation of porcine oocytes. Issue 6 (December 2019) - Yang, Hae-Jun; Lee, Sanghoon; Sim, Bo-Woong; Jeong, Pil-Soo; Choi, Seon-A; Park, Young-Ho; Song, Bong-Seok; Yoon, Seung-Bin; Kang, Philyong; Jeong, Kang-Jin; Kim, Young-Hyun; Huh, Jae-Won; et al.
Abstract : The developmental competence of in vitro -matured oocytes is still lower than that of the in vivo -matured oocytes due to precocious meiotic resumption and inappropriate cytoplasmic maturation. Although numerous efforts have been attempted to accomplish better in vitro maturation (IVM) condition, only limited progress has been achieved. Thus, a current study was conducted to examine the effects of 6-diazo-5-oxo-l-norleucine (DON, an inhibitor of hyaluronan synthesis) during the first half period of IVM on nuclear/cytoplasmic maturation of porcine oocytes and subsequent embryonic development. Based on the observation of the nucleus pattern, metaphase II (MII) oocyte production rate in 1 µM DON group was significantly higher than other groups at 44 h of IVM. The 1 µM of DON was suggested to be optimal for porcine IVM and was therefore used for further investigation. Meiotic arrest effect of DON was maximal at 6 h of IVM, which was supported by the maintenance of significantly higher intra-oocyte cAMP level. In addition, increased pERK1/2 levels and clear rearrangement of cortical granules in membrane of MII oocytes matured with DON provided the evidence for balanced meiosis progression between nuclear and cytoplasmic maturation. Subsequently, DON significantly improved blastocyst formation rate, total cell numbers, and cellular survival in blastocysts after parthenogenetic activation, in vitro fertilization, and somatic cell nuclear transfer. Altogether, our results showed for the first time that 1 µM DON can be used to increase the yield of developmentally competent MII oocytes by synchronizing nuclear/cytoplasmic maturation, and it subsequently improves embryo developmental competence.